1994
DOI: 10.1063/1.870679
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration and scattering of injected electrons in plasma beat wave accelerator experiments*

Abstract: The results from experiments in which a two-frequency CO 2 laser is used to beat-excite large-amplitude, relativistic electron plasma waves in a tunnel-ionized plasma are reported. The plasma wave is diagnosed by injecting a beam of 2 MeV electrons and observing the energy gain and loss of these electrons, as well as the scattering and deflection of the transmitted electrons near 2 MeV. Accelerated electrons up to 30 MeV have been observed. The lifetime of the accelerating structure as seen by small-angle Thom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 10 publications
1
31
0
Order By: Relevance
“…The first configuration is the so-called injector-accelerator, where a ∼ 100 MeV class electron beam produced by a short, high-density injector stage is further accelerated to ∼ GeV level using a second low-density accelerator stage [11,24,25]. The second example is the external injection scheme where a highquality, relativistic electron bunch is first generated using an RF accelerator and then injected into a PBA [26][27][28][29][30]. The third example concerns the proposed PBA driven light source [31][32][33], where a high-quality electron beam needs to be coupled from the plasma wake to an undulator.…”
mentioning
confidence: 99%
“…The first configuration is the so-called injector-accelerator, where a ∼ 100 MeV class electron beam produced by a short, high-density injector stage is further accelerated to ∼ GeV level using a second low-density accelerator stage [11,24,25]. The second example is the external injection scheme where a highquality, relativistic electron bunch is first generated using an RF accelerator and then injected into a PBA [26][27][28][29][30]. The third example concerns the proposed PBA driven light source [31][32][33], where a high-quality electron beam needs to be coupled from the plasma wake to an undulator.…”
mentioning
confidence: 99%
“…An e ect like the Weibel instability already observed in ref. [19] is a good candidate to explain a long term (ns) deviation of the electrons. It could thus explain this BG.…”
Section: Resultsmentioning
confidence: 99%
“…A particular emphasis has been given to the separation of the signal from the background (BG) noise in the design of the experimental apparatus [22] and in the analysis of the data. In the case of LBWA experiments, Clayton et al have shown that magnetic and/or transverse electric elds, due to a Weibel-like instability [19], still exist in the plasma a long (a few nanoseconds) time after the excitation of the EPW. Electrons de ected by such elds can scatter on the walls of the vacuum chamber and fake a signal, as is possibly the case in [20] and in the surprising result of [21].…”
Section: Introductionmentioning
confidence: 99%
“…This led to a wide range of research projects aimed at cleverly inducing the plasma to develop relativistic wakes of nonlinear amplitude, for example, by driving a nonlinear resonance through the beating of two laser beams. [45][46][47][48][49][50] Then in 2002, by means of particle in cell simulations, Pukhov and Meyer-ter-Vehn discovered what is now known as the "bubble regime." In this regime the wake is created directly by a concentration of energy so brief and so intense that it displaces a significant fraction of the electrons as it traverses the plasma.…”
Section: Relativistic Laser Plasmasmentioning
confidence: 99%